The syntax of Spanish - Zagona, Karen T., 1951- (Cambridge syntax guides., 2002)
Clear and well-organised, this textbook is an introduction to Spanish syntax, which assumes no prior knowledge of current theory. Beginning with a descriptive overview of the major characteristics of the grammar, it goes on to describe facts about Spanish, such as its word order, notions of 'subject', 'direct object', 'auxiliary verb' and so on. The book combines traditional grammatical description with perspectives gained from recent research in the Principles and Parameters framework. It also presents useful theoretical notions such as semantic roles, Case, and Predication. Accessibly written, the book gives just enough background so as to allow the reader to understand the lines of investigation that have been pursued in accounting for such issues as clause structure and constituent order. It will be of use to students who are interested in grammar, Spanish, or in some of the basic results of modern, formal linguistic theory.